Wage and employment effects of a wage norm: The Polish transition experience - Alain De Crombrugghe; Gregory De Walque (National Bank of Belgium, 2011)
Most transition countries used tax-supported wage norms in the early 1990's, as a part of their market liberalization programs. This paper analyses how a firm-level tax (or subsidy) on deviations from a pre-set wage norm may promote employment by rotating the labor demand curve perceived by the workers' union around the value of the norm. We derive the conditions such that it yields a positive employment effect. We test the effect of the norm on the wages on a sample of Polish firms in 1990 and 1991. The data support the role of the wage norm on the position of the perceived labor demand and the role of the tax rate on its slope.
Keywords: H23; J23; J5; P31; 330; transition economies; labor market; unions; excess wage tax; employment; Arbeitsmarkt; Arbeitsnachfrage; Lohnbildung; Staatliche Einflussnahme; Gewerkschaft; Beschäftigungseffekt; Polen